The influence of foundation restoration type and ceramic thickness on the final color of zirconia-reinforced lithium silicate ceramic - Saeed Nikanjam; Soudeh Tayebi (Wolters Kluwer Medknow Publications, 2023)
Background: Similarity in the appearance of a monolithic restoration with the adjacent teeth is necessary. This study aims to influence the foundation material type and ceramic thickness on the final color of zirconia-reinforced lithium silicate (ZLS) ceramic. Materials and Methods: In this experimental study, the A2 translucent blocks of ZLS were sectioned into rectangular specimens with thicknesses 1, 1.5, and 2 mm (n = 15). Substructure materials include resin composite (B1, D2, A2, A3, and C3), nickel chrome alloy, amalgam, and white and black substrate. Substructure material of resin composite with A2 color was proposed as the control group. The value of the color difference (ΔE00) is calculated by the CIEDE2000 formula. Data analysis was accomplished by two-factor repeated measures ANOVA and one-sample t-test (α =0.05). Results: The mean value of maximum ΔE00 with a black substrate (12.13 ± 0.17) at 1 mm ceramic thickness and the mean value of minimum ΔE00 with B1 resin composite foundation material (0.02 ± 0.17) at 2 mm ceramic thickness are visible. The significant effect of the foundation restoration type, thickness, and interaction between them is visible on ΔE00 (P < 0.001). Conclusion: Different thickness is required to meet ideal esthetic outcomes with different substrates. Under the conditions of this investigation, zirconia-reinforced lithium silicate over black, white, nickel-chromium, and amalgam did not meet acceptable outcomes.